Multiobject Reliability Analysis of Turbine Blisk with Multidiscipline under Multiphysical Field Interaction - Chun-Yi Zhang; Cheng Lu; Cheng-Wei Fei; Ling-Jun Liu; Yat-Sze Choy; Xiang-Guo Su (Advances in Materials Science and Engineering)
To study accurately the influence of the deformation, stress, and strain of turbine blisk on the performance of aeroengine, the comprehensive reliability analysis of turbine blisk with multiple disciplines and multiple objects was performed based on multiple response surface method (MRSM) and fluid-thermal-solid coupling technique. Firstly, the basic thought of MRSM was introduced. And then the mathematical model of MRSM was established with quadratic polynomial. Finally, the multiple reliability analyses of deformation, stress, and strain of turbine blisk were completed under multiphysical field coupling by the MRSM, and the comprehensive performance of turbine blisk was evaluated. From the reliability analysis, it is demonstrated that the reliability degrees of the deformation, stress, and strain for turbine blisk are 0.9942, 0.9935, 0.9954, and 0.9919, respectively, when the allowable deformation, stress, and strain are 3.7 × 10−3 m, 1.07 × 109 Pa, and 1.12 × 10−2 m/m, respectively; besides, the comprehensive reliability degree of turbine blisk is 0.9919, which basically satisfies the engineering requirement of aeroengine. The efforts of this paper provide a promising approach method for multidiscipline multiobject reliability analysis.